Development of Android-Based Learning Media Using Microsoft Powerpoint Integrated Ispring Suite on Class X's Work and Energy Materials - Fransisca Stevani; Imam Sucahyo (IKIP Mataram, 2022)
Learning is directly realized from the interaction process between educators and students, supported by learning resources, learning media, and other learning components. As time progressed, various learning problems, especially physics subjects were found, for example, the Covid-19 pandemic, which made it difficult for educators to provide and deliver material to students in class. This study aims to produce valid, practical, and effective android-based interactive learning media on work and energy materials. This learning media uses the ADDIE development method with stages up to Implementation only. After developing the product, the researcher used an assessment questionnaire to determine the product's validity from the media and material aspects. After that, the researcher tested it on physics subject teachers and 36 students at SMAN 14 Surabaya to determine the practicality and effectiveness of learning media. The results of the study obtained the value of media and material validity with an average percentage of 78.5% in the appropriate category, the practicality of the media obtained an average percentage of 93.5% in the very practical category, and the effectiveness of the media can be seen from the increase in learning outcomes students who get the effectiveness of 0.70 in the high category. Thus it can be concluded that the media is feasible and practical to use in the learning process and is very effective in motivating students to learn physics.